Research and development management : technology journey through analysis, forecasting and decision making - Daim, Tugrul Unsal, 1967-; Kim, Jisun, 1973-; Phan, Kenny (Springer, 2017)
This book introduces readers to essential technology assessment and forecasting tools, demonstrating their use on the basis of multiple cases. As organizations in the high-tech industry need to be able to assess emerging technologies, the book presents cases in which formal decision-making models are developed, providing a framework for decision-making in the context of technology acquisition and development. Applications of different technology forecasting tools are also discussed for a range of technologies and sectors, providing a guide to keep R & D organizations abreast of technological trends that affect their business. As such, the book offers a valuable the theoretical and practical reference guide for R & D managers responsible for emerging and future technologies.
Keywords: Technological innovations -- Management.; Industrial management.; Technological forecasting.; Technology assessment.; Decision making.; elektronické knihy; electronic books